Coagulation States in Patients With Sudden Sensorineural Hearing Loss Evaluated by Thromboelastography. (3rd November 2020) - Li, Chunyan; Zhou, Huiqun; Feng, Yanmei; Zhao, Yan; Wang, Jingjing; Chen, Zhengnong; Yin, Shankai
Abstract : Objective: The state of coagulation is controversial in patients with sudden sensorineural hearing loss (SSNHL). We used thromboelastography (TEG) to explore the relationships between blood coagulation parameters and SSNHL pathogenesis and recovery. Study Design: Prospective study. Setting: Affiliated Sixth People's Hospital, Shanghai Jiao Tong University. Methods: A total of 104 newly diagnosed patients with SSNHL and 29 matched healthy controls were recruited. Hearing assessments, TEG, and conventional coagulation tests (CCTs) were performed, followed by standard treatments and follow‐up. Results: The TEG parameters of patients with SSNHL were in the normal range, but the group exhibited a significantly prolonged kinetic time (K; P =. 004) and a smaller angle ( P =. 003) as compared with the controls. After grouping the patients with SSNHL according to audiograms and comparing them in pairs, we found that the differences were significant only when controls were compared with patients with low‐frequency SSNHL (K, P =. 023; angle, P =. 04) and flat‐type SSNHL (K, P =. 017; angle, P =. 014). Logistic regression analysis showed that neither TEG nor CCT parameters significantly affected hearing improvement after SSNHL treatment. Conclusions: Although the K value and angle were significantly increased and significantly reduced, respectively, in the test group as compared with the control group, the state of coagulation in patients with SSNHL was still within the normal range. No CCT or TEG coagulation parameters (except the angle) differed significantly among patients in each group according to hearing recovery status, which suggested that the coagulation status does not determine the prognosis of patients with SSNHL.